Social tourism and well-being in later life. (May 2015) - Morgan, Nigel; Pritchard, Annette; Sedgley, Diane
Highlights: Discusses tourism and economically disadvantaged older people's well-being. Explores the respite and companionship value of social tourism for economically disadvantaged older people. Reveals tourism as a space for renegotiation of self post-bereavement. Suggests a future research agenda on older people's social tourism experiences. Abstract: Studies of social tourism have concentrated on the benefits for young families and people with disabilities, yet few analyses have investigated its wellbeing value for economically disadvantaged older people. Based on participant-driven interviews during a UK social tourism trip, this paper informs understandings of social tourism experiences and explores the links between wellbeing and social tourism opportunities for older people. It reveals that social tourism presents older individuals with occasions for escape, respite, companionship, and reminiscence and for renegotiation of self-identity following spousal bereavement, but that these trips can be anxiously anticipated. The study proposes a research agenda, which explores the physiological, psychological, social and spiritual impacts of social tourism on older people's wellbeing.